Readiness of Green Skill Implementation among Welding Program Students at Public Skill Training Center - Chang, Vui Seng Wilson; Lai, Chee Sern; Abdul Razak, Muhammad Hariz Akmal (Online Journal for TVET Practitioners, 2025)
In recent years, green skills have begun to receive significant attention and are increasingly taken seriously by the public, driven by the rapid advancement of green technologies globally, including in Malaysia. In response to this trend, the present study was conducted to assess the awareness and readiness to implement green skills among students enrolled in the Welding Technology Program at a Public Skills Training Center (ILKA) in Batu Pahat. A total of 101 Welding Technology Program students participated in the study. Descriptive analysis, including mean and standard deviation, was employed to analyze the data. The reliability coefficient for the research instrument was high, α = 0.94. Overall, the findings indicate a highly encouraging level of awareness of green skills among the students, with the majority demonstrating a strong personal awareness of green skill implementation at ILKA. In terms of knowledge, the level of implementation of green skills was also positive, as most respondents agreed with the items assessing their understanding of green concepts. Similarly, students showed favorable attitudes toward green skills, further reinforcing their readiness to adopt environmentally responsible practices. In conclusion, the results of this study demonstrate that welding students at the ILKA exhibit a commendable level of readiness to implement green skills, both in knowledge and attitude, reflecting their potential to contribute effectively to the green industry.